DEPOSITIONAL ENVIRONMENT ANALYSIS AND POTENTIAL RESOURCE DETERMINATION OF J INTERVAL FOR WELL DEEPENING, FIELD A, CENTRAL SUMATRA BASIN, RIAU - RAHMAN RIFANI , ABDUL
Study area is located on A Field, an oil field in Riau Province, Central Sumatra Basin, which consists an area of Ã‚Â± 22 km2. The study was conducted on J interval of the reservoir, which is a part of Bangko Formation. Objectives of the study is to determine geological settings specifically lithology, architectural facies, depositional environment, geometry of reservoir interval, quality and resource potential of interval J of the reservoir. The data used in this study consists of core of 5 wells, wireline logs of 353 wells, and biostratigraphy of 3 wells. In order to achieve the objectives, several methods were used, which are core data analysis, sequence stratigraphy correlation and electrofacies of wireline logs data validated with biostratigraphy data, quality determination, calculation and mapping of petrophysical property, and finally potential hydrocarbon resource determination of J interval of the reservoir. Results of the methods applied are as follows. J interval of the reservoir, part of Bangko Formation, was deposited in Early Miocene on estuarine depositional environment, which facies associations are estuarine channel, tidal mudflat, and marine shale. The geometry of studied interval of reservoir shows that the deposition of estuarine channel has a direction of NE-SW. The quality of the reservoir interval is fair with mean values of effective porosity of 0.32, permeability of 400 mD, and effective water saturation of 0.4. The sum of hydrocarbon resource in the study area is 106 MMBO and the location with the highest potential is located at the southern part of the area, which volume is 44 MMBO.